1899 U.S. Stat. 1270, ch. 429, § 117 - (:unkn) unknown (My University, 1899)
Prohibited concealed carry of any revolver, pistol, other firearm, or knife, dirk, dagger, slung shot, metal knuckles, or any instrument which could inflict injury.
Keywords: CARRY - CONCEALED